Anatomia, taxonomia e filogenia de Siriusgnathus niemeyerorum (Eucynodontia, Traversodontidae) do Triássico Superior sul-brasileiro - Pavanatto, Ane Elise Branco (2019)
This thesis provides information of new traversodontid cynodont taxon, Siriusgnathus niemeyerorum, which is closely related to Exaeretodon, although the new taxonomic unit shows a unique combination of features not present in other cynodonts: two upper incisors; distal accessory labial cusp of upper postcanines more labially placed in comparison with Exaeretodon; two/three lower incisors; rostrum short, broad with almost the same length of the temporal region; postorbital bar more anteriorly positioned than in Exaeretodon; descending process of the jugal incipient; posteriormost border of zygomatic process of squamosal, short and rounded; lambdoidal crest not forming a concavity such as that present in Exaeretodon; and an anteroposteriorly short basicranium. S. niemeyerorum was found in a new Upper Triassic fossiliferous outcrop (Santa Maria Supersequence) of Southern Brazil, the Niemeyer Site, which lithology is consistent with that of the Candelária Sequence. This new locality presents a high prevalence of traversodontid cynodonts. The majority of the collected specimens are mostly composed of isolated bones and fragmentary specimens, but also including well-preserved skulls and lower jaws. Probainognathian cynodonts and archosauromorphs are also present, but they are rare in comparison with the records of traversodontids. The specimens collected so far were grouped into Voorhies Groups. There is a predominance of Voorhies Group III and the Group II the less represented (Group III > Group I > Group II). Some specimens display evidence of ichnological activity of invertebrate scavengers. Given that so far no confirmed traversodontids recorded in the uppermost levels of the Candelária Sequence, we suggest a Carnian age for the new outcrop. The holotype of S. niemeyerorum (CAPPA/UFSM 0032) as well as two specimens of Exaeretodon riograndensis (CAPPA/UFSM 0030 e 0227), were scanned in a medical tomograph, in order to access its internal structures, to investigate the endocranial morphology of both taxa. After the segmentation of endocranial cavities and generation of the 3D models, it was observed that the endocasts were elongated and tubular, without a clearly division between the cerebral regions. In both taxa, a longitudinal sulcus dividing, the olfactory bulbs and the cerebral hemispheres are absent. The unossified zone is well developed and the pineal tube is absent. S. niemeyerorum has a well delimited hypophyseal fossa, whereas in E. riograndensis it is not well delimited. Encephalization Quotients was calculated to each specimen, resulting in higher values than the observed in other traversodontids, probably because technic differences employed to obtain the endocast volume. Overall, the endocast morphology of S. niemeyerorum and E. riograndensis is similar to described to others cynodonts. This study provide the first data about the endocranial morphology of traversodontids through tomography.